Squamous Cancer of the Esophagus in Africa: A Causal Pathway Established - Sammon, Alastair M (Asian Pacific Journal of Cancer Biology, 2022)
Squamous cancer of the esophagus has been endemic in much of East, Central and Southern Africa since the 1940s. Much research has concentrated on attempts to identify major carcinogenic influences, and failure to do so has made it clear that the problem in high incidence areas (HIAs) is not primarily of potent environmental carcinogens, but of population susceptibility. In Africa the association with maize is constant and strong. Research in the last decade has helped to explain that association. Considered along with historical findings there is now enough evidence to establish causal associations of a nutritionally deficient maize diet and use of maize meal with squamous cancer of the esophagus. Evidence is available in a high incidence area of degenerating maize meal resulting in excess production of PGE2, gastric hypochlorhydria and a predominant pattern of non-acid gastroesophageal reflux. This pathway explains the existence of major population susceptibility: a poor maize-based diet provides specific nutritional deficiencies and n-6 fatty acid dominance which cause failure of homeostasis of the arachidonic acid cascade; with this background chemically degenerating maize meal then triggers duodenogastric reflux and non-acid gastro-esophageal reflux; non-acid reflux causes squamous cancer of the esophagus. Within a susceptible population, environmental carcinogens including tobacco increase individual risk. There is sufficient evidence that this is an active pathway, and the dominant pathway to SCCE in high incidence areas in Africa.There is sufficient evidence to justify appropriate preventative measures.